CLIMATE: IS THE PAST THE KEY TO THE FUTURE? - Hay W.W.; DeConto R.M.; Wold Ch.N. (My University, 1997)
The climate of the Holocene is not well suited to be the baseline for the climate of the planet. It is an interglacial, a state typical of only 10% of the past few million years. It is a time of relative sea-level stability after a rapid 130-m rise from the lowstand during the last glacial maximum. Physical geologic processes are operating at unusual rates and much of the geochemical system is not in a steady state. During most of the Phanerozoic there have been no continental ice sheets on the earth, and the planet’s meridional temperature gradient has been much less than it is presently. Major factors influencing climate are insolation, greenhouse gases, paleogeography, and vegetation; the first two are discussed in this paper. Changes in the earth’s orbital parameters affect the amount of radiation received from the sun at different latitudes over the course of the year. During the last climate cycle, the waxing and waning of the northern hemisphere continental ice sheets closely followed the changes in summer insolation at the latitude of the northern hemisphere polar circle. The overall intensity of insolation in the northern hemisphere is governed by the precession of the earth’s axis of rotation, and the precession and ellipticity of the earth’s orbit. At the polar circle a meridional minimum of summer insolation becomes alternately more and less pronounced as the obliquity of the earth’s axis of rotation changes. Feedback processes amplify the insolation signal. Greenhouse gases (H2O, CO2, CH4, CFCs) modulate the insolation-driven climate. The atmospheric content of CO2 during the last glacial maximum was approximately 30% less than during the present interglacial. A variety of possible causes for this change have been postulated. The present burning of fossil fuels, deforestation, and cement manufacture since the beginning of the industrial revolution have added CO2 to the atmosphere when its content due to glacial-interglacial variation was already at a maximum. Anthropogenic activity has increased the CO2 content of the atmosphere to 130% of its previous Holocene level, probably higher than at any time during the past few million years. During the Late Cretaceous the atmospheric CO2 content was probably about four times that of the present, the level to which it may rise at the end of the next century. The results of a Campanian (80 Ma) climate simulation suggest that the positive feedback between CO2 and another important greenhouse gas, H2O, raised the earth’s temperature to a level where latent heat transport became much more significant than it is presently, and operated efficiently at all latitudes. Atmospheric high- and low-pressure systems were as much the result of variations in the vapor content of the air as of temperature differences. In our present state of knowledge, future climate change is unpredictable because by adding CO2 to the atmosphere we are forcing the climate toward a “greenhouse” mode when it is accustomed to moving between the glacial–interglacial “icehouse” states that reflect the waxing and waning of ice sheets. At the same time we are replacing freely transpiring C3 plants with water-conserving C4 plants, producing a global vegetation complex that has no past analog. The past climates of the earth cannot be used as a direct guide to what may occur in the future. To understand what may happen in the future we must learn about the first principles of physics and chemistry related to the earth’s system. The fundamental mechanisms of the climate system are best explored in simulations of the earth’s ancient extreme climates.
Keywords: Campanian; Cretaceous; Holocene; Mesozoic::Cretaceous; Кайнозой::Четвертичная::Голоцен; Mesozoic::Cretaceous::Upper::Campanian; Мезозой::Меловая::Верхний::Кампанский; Cenozoic::Quaternary::Holocene; Мезозой::Меловая